A hipótese do contínuo entre o léxico e a gramática e as construções incoativa, medial e passiva do PB - Larissa Santos Ciriaco (2011)
This dissertation aims to study the Brazilian Portuguese (BP) inchoative, middle and passive constructions. The main issue at hand refers to the fact that not all verbs can instantiate these constructions. Therefore, we raise the question of why it is so, and what kind of linguistic knowledge is at stake when we face these facts of language. To answer those questions, we adopt the hypothesis that the inchoative, middle andpassive patterns are constructions, independent units of language, being described as an association of form and meaning. If that hypothesis is correct, the meaning associated to those clausal patterns is responsible for the fact that only certain verbs are able to instantiate them. Adopting Construction Grammar (Goldberg, 1995, 2006) as a theoretical background, we assume that only semantic compatible verbs can instantiate the BP inchoative, middle and passive constructions. Hence, this research aims to characterize the constructions under study, and to provide a representation for their meaning. In order to circumscribe the verb classes associated to each of them, it was conducted a descriptive analysis where some verb classes were analyzed in relation tothe inchoative, middle and passive constructions. The Construction Grammar theory was articulated to the semantic decomposition of verbs, used as an instrument for determining the constructions` meanings. Through observation of the semantic compatible verb classes meaning, we were able to isolate the meanings of inchoative, middle and passive constructions, and therefore attribute a representation to each ofthem. In conclusion, this research brings positive evidence for the hyphothesis adopted, showing that inchoative, middle and passive are clausal patterns that can be described as constructions, and therefore explain the BP data.